Late Campanian-Early Maastrichtian Vertebrates From The James Ross Basin, West Antarctica: Updated Synthesis, Biostratigraphy, And Paleobiogeography - Reguero, Marcelo Alfredo (2022)
The Snow Hill Island Formation (SHIF; late Campanian-early Maastrichtian) crops out in the northeast of the Antarctic Peninsula and constitutes the basal part of the late Campanian-early Maastrichtian sedimentary succession of the James Ross Basin (NG Sequence). Its major exposures occur at the James Ross and Vega islands. Several fossil-bearing localities have been identified in the SHIF providing a valuable fauna of invertebrates and vertebrates, and flora. Our study focuses on the vertebrate fauna recovered at Gamma and Cape Lamb members of the SHIF. The marine vertebrate assemblages include chondrichthyans, actinopterygians, and marine reptiles (elasmosaurid plesiosaurs and mosasaurs). A diverse terrestrial vertebrate assemblage has been reported being characterized by dinosaurs (sauropod, elasmarian ornithopods, nodosaurid ankylosaur, and a paravian theropod), pterosaurs and birds. Most SHIF dinosaurs share close affinities with penecontemporaneous taxa from southern South America, indicating that at least some c6ontinental vertebrates could disperse between southern South America and Antarctica during the Late Cretaceous. The Snow Hill Island Formation provides the most diverse Late Cretaceous marine and continental faunas from Antarctica. The present study summarizes previous and new vertebrate findings with the best actualized stratigraphical framework, providing a more complete fauna association and analyzing further perspectives.